The design and discovery of T-type calcium channel inhibitors for the treatment of central nervous system disorders - Choi, Kee-Hyun (INFORMA HEALTHCARE, 2013)
Introduction: Neuronal T-type calcium channels (T-type channels) are expressed throughout the central nervous system (CNS), regulating neuronal excitability. T-type channels in the CNS are involved in various neurophysiological and pathophysiological states, and thus have become a promising therapeutic target. Areas covered: This article discusses T-type channel-related CNS disorders such as epilepsy, neuropathic pain, insomnia and tremor disorders including Parkinson's disease. In addition, the article reviews T-type channel inhibitors showing efficacy in animal models in such CNS disorders, with a focus on classical T-type channel inhibitors with limited specificity for T-type channels as well as novel inhibitors with high specificity. Furthermore, the article also presents and discusses the next generation of T-type channel inhibitor discovery, virtual as well as screening and high-throughput screening techniques. Expert opinion: Although T-type channel-related CNS disorders seem to be diverse, it converges into the one major cause - abnormal hyperactivity of neurons. T-type channel-specific inhibitors could thus be commonly applied for the treatment of such CNS disorders regardless of the complexity of individual disorder. Structural information of inhibitor-binding sites would facilitate the discovery of the next generation of T-type channel-specific inhibitors by stimulating structure-based rational drug designs.
Keywords: RAT SENSORY NEURONS; 5-ALPHA-REDUCED NEUROACTIVE STEROIDS; CHILDHOOD ABSENCE EPILEPSY; CA2+ CHANNELS; IN-VITRO; THALAMIC NEURONS; ESSENTIAL TREMOR; UP-REGULATION; PARKINSONS-DISEASE; NEUROPATHIC PAIN